Platelets, immune-mediated thrombocytopenias, and fetal hemorrhage. Issue 141 (May 2016) - Xu, Xiaohong Ruby; Gallant, Reid C.; Ni, Heyu
Abstract: Platelets are small versatile blood cells generated from megakaryocytes in the bone marrow and cleared in the reticuloendothelial system. Platelet accumulation (adhesion and aggregation) at the site of injury has been considered the first wave of hemostasis. Interestingly, although fibrinogen and von Willebrand factor (VWF) are documented to be essential for hemostasis, fibrinogen/VWF-independent platelet aggregation and thrombosis still occur. Following platelet activation and phosphatidylserine expression, platelets also contribute to cell-based thrombin generation and blood coagulation – the second wave of hemostasis. Most recently, deposition of fibronectin and other plasma proteins onto the injured vessel wall was identified as a "protein wave" of hemostasis, in which platelets may release their granule proteins and thus also contribute to this very early hemostatic event. Due to the central roles of platelets in hemostasis, excessive platelet clearance may lead to bleeding disorders as observed in auto- and alloimmune-mediated thrombocytopenias. In this review, we will introduce several new pathways of thrombosis and hemostasis as well as antibody Fc-independent platelet clearance, which may play an important role in immune-mediated thrombocytopenias. We will also discuss the roles of platelets in fetal hemostasis that may deserve further investigation.